Multifaceted Clinical Effects of Echinochrome - Hyoung Kyu Kim; Elena A. Vasileva; Natalia P. Mishchenko; Sergey A. Fedoreyev; Jin Han (Marine Drugs, 2021)
The marine drug histochrome is a special natural antioxidant. The active substance of the drug is echinochrome A (Ech A, 7-ethyl-2,3,5,6,8-pentahydroxy-1,4-naphthoquinone), the most abundant quinonoid pigment in sea urchins. The medicine is clinically used in cardiology and ophthalmology based on the unique properties of Ech A, which simultaneously block various links of free radical reactions. In the last decade, numerous studies have demonstrated the effectiveness of histochrome in various disease models without adverse effects. Here, we review the data on the various clinical effects and modes of action of Ech A in ophthalmic, cardiovascular, cerebrovascular, inflammatory, metabolic, and malignant diseases.